Implementasi Kebijakan Program Agropolitan di Provinsi Kepulauan Bangka Belitung - Rully Redhani; Bambang Satria (Sawala : Jurnal Administrasi Negara, 2020)
In developing the agricultural sector, the potential of the Bangka Belitung Islands Province as an agricultural area has been stipulated in the Regional Spatial Plan (RTRW) of the Province of Bangka Belitung Islands for 2014-2034. This research is entitled Implementation of Agropolitan Program in Bangka Belitung Islands Province. The purpose of this study was to determine how to implement agropolitan programs in Bangka Belitung and to identify supporting factors for agropolitan programs in Bangka Belitung. The benefits of this research can provide insight and contribution of thought to the development of state administration science, especially public policy, namely on policy implementation. This study used qualitative research methods. Data collection techniques using interviews, observation and documentation. The results showed that the implementation of the agropolitan program policy in the Province of Bangka Belitung Islands had gone well. This is indicated by very clear communication carried out by the policy implementer. The recommendation given is to provide understanding to the implementing apparatus and farmers so that they can follow the stages of the agropolitan program by applying the existing standard operating procedures, starting from conducting socialization, workshops or training on the correct application of SOPs.